INVESTIGATION OF THE SYNTHESIS OF ACETYLENE AMINO ALCOHOLS AND THE STUDY OF THEIR BIOLOGICAL ACTIVITY - Juraboev, Fozil (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This work describes the synthesis of acetylene amino alcohols based on the aminomethylation of secondary acetylene alcohols in a 1,4-dioxane solvent medium, using formaldehyde and hydroxyl-containing or heterocyclic amino compounds under the catalysis of copper(I) salts. Hex-1-yn-3-ol was used as a secondary acetylene alcohol, and amines such as monoethanolamine, diethanolamine, and morpholine were used as aminating agents. As a result of the conducted research, amino alcohols with high yields were synthesized. The results of studies on the use of the obtained acetylene amino alcohols in agriculture are presented. The biostimulating effect of synthesized acetylene amino alcohols has been studied. Their positive effect on the germination of wheat seeds and an increase in yield has been established.